2003
DOI: 10.1063/1.1592613
|View full text |Cite
|
Sign up to set email alerts
|

Friction force microscopy using silicon cantilevers covered with organic monolayers via silicon–carbon covalent bonds

Abstract: Cantilevers covered with hydrocarbon (CH) and fluorocarbon (CF) monolayers via Si–C covalent bonds were prepared and used for adhesion force measurements and friction force microscopy of the surface patterned also with CH and CF areas. The adhesion and friction forces on CF areas were larger than those on CH areas, especially using CF cantilevers. Large polarizabilities of CF molecules compared to CH molecules are found to enhance the contrast in adhesion and friction images. The cantilevers covered with organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Unfortunately, this surface readily adsorbs contaminants because of its relatively high surface energy. UV radiation can also be used to bind hydrocarbons or fluorocarbons to tip surfaces [144].…”
Section: Modificationmentioning
confidence: 99%
“…Unfortunately, this surface readily adsorbs contaminants because of its relatively high surface energy. UV radiation can also be used to bind hydrocarbons or fluorocarbons to tip surfaces [144].…”
Section: Modificationmentioning
confidence: 99%
“…Several other methods for covalent attachment of functionalized monolayers have been investigated in detail since then (Table 1):1) formation of siloxane self-assembled monolayers on silicon nitride AFM probes with [23] and without [24] surface oxide layer and on tungsten probes [25]; 2) attachment of alkyl monolayers on silicon probes with direct Si-C bond [26], and 3) functionalization of carbon nanotube (NT) probes [27,28]. We found that the use of silver instead of gold produces similar results in CFS [29].…”
Section: Chemical Functionalization Of Force Probesmentioning
confidence: 99%
“…Hydrosilylated silicon offers significant potential to provide highly functional surfaces for a variety of industrial applications including anti‐stiction coating films for polysilicon MEMs,49 monolayer templates,19,46,50–54 bioderivative arrays,55 stabilizers for porous silicon,2,23,56 molecular electronic devices,26,57 and capsulators of silicon nanocrystals 58. This section describes recent progress in the development of these technological applications.…”
Section: Technological Applicationsmentioning
confidence: 99%
“…Highly resolved patterns formed of SiC linked monolayers have performed as chemical templates for the area‐selective fabrication of molecular electronic devices, biochips, bioarrays, and chemically based inorganic devices. A wide variety of lithography techniques including photolithography,19,46,54 electron beam lithography, reagentless lithography,50 anodic oxidation,51,53 and scanning probe‐induced cathodic electrografting52,59 have been applied to fabricate such monolayer templates. A chemical template with microscale domains can easily be achieved through conventional photolithography, the most well‐developed technique, directly through a photomask.…”
Section: Technological Applicationsmentioning
confidence: 99%